Analisis Pengaruh Aliran Kas Bebas Positif Dan Negatif, Dividen Dan Leverage Terhadap Nilai Pemegang Saham Studi Kasus: Perusahaan Non Keuangan Yang Terdaftar di Bursa Efek Indonesia Periode 2003 â 2010 - Sasongko, Hendro; Achsani, Noer Azam; Sembel, Roy; Kusumastanto, Tridoyo (Jurnal Ilmiah Ranggagading (JIR), 2012)
Free cash flow is viewed as performance parameter thatâs more promising because itâs more transparent in presenting operational activity, investment, and companyâs funding. Besides those advantages, there are two questions: (1) is the free cash flow able to become determinant against stockholdersâ value and (2) are there other factors which affect it? This study took sample from 184 non-finance companies registered at Indonesia Stock Exchange period 2003 â 2010, using double regression analysis method. The result of this study shows that negative free cash flow, dividend, and leverage has significant influence against stockholdersâ value.